THE EFFECT OF PLANTING TIME ON THE GROWTH OF MASH - Aralova Minavvar Nomoz qizi; Abdusamadov Abdulaziz Abdunabi o‘g‘li (Scholar Express Journal, 2023)
This article analyzes the changes in the yield of mung bean at different times and the results of the study of the formation of protein in mung bean
Keywords: Mash; protein; sowing time